Metabolic impacts of cordycepin on hepatic proteomic expression in streptozotocin-induced type 1 diabetic mice. - Kongphop Parunyakul (Public Library of Science (PLoS), 2021)
Type 1 Diabetes mellitus (T1DM) is associated with abnormal liver function, but the exact mechanism is unclear. Cordycepin improves hepatic metabolic pathways leading to recovery from liver damage. We investigated the effects of cordycepin in streptozotocin-induced T1DM mice via the expression of liver proteins. Twenty-four mice were divided into four equal groups: normal (N), normal mice treated with cordycepin (N+COR), diabetic mice (DM), and diabetic mice treated with cordycepin (DM+COR). Mice in each treatment group were intraperitoneally injection of cordycepin at dose 24 mg/kg for 14 consecutive days. Body weight, blood glucose, and the tricarboxylic acid cycle intermediates were measured. Liver tissue protein profiling was performed using shotgun proteomics, while protein function and protein-protein interaction were predicted using PANTHER and STITCH v.5.0 software, respectively. No significant difference was observed in fasting blood glucose levels between DM and DM+COR for all time intervals. However, a significant decrease in final body weight, food intake, and water intake in DM+COR was found. Hepatic oxaloacetate and citrate levels were significantly increased in DM+COR compared to DM. Furthermore, 11 and 36 proteins were only expressed by the N+COR and DM+COR groups, respectively. Three unique proteins in DM+COR, namely, Nfat3, Flcn, and Psma3 were correlated with the production of ATP, AMPK signaling pathway, and ubiquitin proteasome system (UPS), respectively. Interestingly, a protein detected in N+COR and DM+COR (Gli3) was linked with the insulin signaling pathway. In conclusion, cordycepin might help in preventing hepatic metabolism by regulating the expression of energy-related protein and UPS to maintain cell survival. Further work on predicting the performance of metabolic mechanisms regarding the therapeutic applications of cordycepin will be performed in future.